Velocidade de semeadura e profundidade da haste em sistema plantio direto de milho e soja - Cavichioli, Fabio Alexandre [UNESP] (2014)
No tillage is a reality in Brazilian agriculture, which is growing every year, modernization and study of the subject being required increasingly facing new aggregate machinery mechanisms. This system is characterized by less intensive tillage, and by reducing the frequency of agricultural machinery traffic on the ground, and remain on the surface of even greater amount of plant mass, which characterizes it as a conservationist. Crops of corn and soybeans have high yield potential and can reach high yields. The objective of this thesis to study the possible interaction between travel speeds of the tractor assembly / seeder and depths of the planter chisel tillage corn and soybeans. The experiment was conducted in the agricultural years 2010/11 and 2011/12 and was conducted in the area of Finance of Education, Research and Production, UNESP / Jaboticabal, the soil of the experimental area was classified as Typic typical Eutroferric The moderate clayey, with a 2x3 factorial conducted in a randomized block design with six treatments and four replications, for a total of 24 experimental plots of 300 m². The treatments consisted of two velocities of the tractor / seeder (4,5 and 6,5 km h-1), combined with three working depths of planter chisel fertilizer (10, 12,5 and 15 cm), for the sowing of corn and soybeans. The results showed that the variation in travel speed in the operation of maize sowing did not affect the longitudinal distribution of seedlings, initial stand, grain yield and demand for fuel. The tractor demanded greater power drawbar pull and power in the operation of sowing corn and soybeans when using the speed 6,5 km h-1, working with the depth 15 cm of the planter chisel. The use of higher travel speed of the tractor / seeder and set the working depth of the lower planter chisel provided less power demand set and trailed the same productivity of maize. The speed of 6,5 km h-1 ally working depth of 12,5 cm rods is indicated ...